An embedded 4(3) pair explicit two derivative Runge-Kutta-Nyström method for solving y″(x) = f(x, y, y′). (November 2018) - Mohamed, T S; Senu, N; Nik Long, N M A; Ibrahim, Z B
Abstract: In this paper, we present a pair of two derivative Runge-Kutta-Nyström method for solution of second-order ordinary differential equations(ODEs) of the form y ″( x ) = f ( x, y, y ′) denoted as ETDRKN method. The pair has two stages and algebraic orders four and three. The techniques used in the derivation of the method is that the higher order method is very precise and the lower order method give the best error estimate. The experimental results show the efficiency of the proposed method in comparison with the well-known embedded Runge-Kutta pairs in the scientific literature.